Meta-Analysis of the Effect of an Integrated Science Book to Increase Students' Knowledge - Putri, Nurul Hasanah Daniyah (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The purpose of this study is to see the effect size of the effect book of integrated science teaching materials to increase the knowledge of students, where this study uses the meta-analysis method. The articles obtained in this study amounted to 20. The results of this study were first that an integrated science book has high effectiveness in increasing the knowledge of students. Second, if it is seen based on its classification, pocket books have the highest effectiveness for increasing students' knowledge. Third, the integrated science book is effectively used to increase the knowledge of students at all levels of education. Fourth, the theme of chemicals in life is effectively used to increase learners' knowledge.